2021
DOI: 10.1016/j.bbih.2021.100359
|View full text |Cite
|
Sign up to set email alerts
|

The role of the immune system in postpartum psychosis

Abstract: Postpartum psychosis is the most severe psychiatric disorder associated with childbirth. The risk is particularly high for women with a history of bipolar disorder or schizoaffective disorder, or those who have suffered a previous episode of postpartum psychosis. However, the aetiology of the illness remains unclear. Pregnancy and the early postpartum are times of significant immunological change. Furthermore, alterations to the immune system have been implicated in the onset and course of various psychopathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…Immune system dysfunction may also be implicated in PPP, although some have noted that it is unclear whether the immune system dysfunction is implicated in the etiology of PPP or rather a sequela of PPP [ 27 ]. Dazzan et al proposed that T cells and their effect on brain myelination may be implicated in PPP [ 28 ] based on clinical and animal studies.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Immune system dysfunction may also be implicated in PPP, although some have noted that it is unclear whether the immune system dysfunction is implicated in the etiology of PPP or rather a sequela of PPP [ 27 ]. Dazzan et al proposed that T cells and their effect on brain myelination may be implicated in PPP [ 28 ] based on clinical and animal studies.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Immunologic changes during pregnancy and postpartum often lead to immune dysfunction, and studies have shown that women with postpartum psychosis display increased monocytes, decreased T-cells, and an up-regulation in immune-related genes compared to controls. 12 Similarly, immune dysfunction also increases susceptibility to autoimmune conditions and infections during the postpartum period. 13 Hormonal fluctuations are ubiquitous in pregnancy with the rise in progesterone and estrogen during pregnancy to prepare the body for growth and maturation of the fetus, and a dramatic decrease during the postpartum period.…”
Section: What Is the Etiology Of Delirium With Dysautonomia In This P...mentioning
confidence: 99%
“…A role for immune dysregulation in PP is supported by evidence showing that women who experience PP have higher rates of other complications related to immune dysfunction during their pregnancy ( 130 ). For example, immune imbalance occurs in preeclampsia and preeclampsia is a significant risk factor in later developing first onset PP ( 131 ).…”
Section: Postpartum Psychosismentioning
confidence: 99%
“…A growing literature points to links between immune alterations and the development of PP in otherwise healthy mothers ( 130 ). One study assessed circulating immune cell types in a population of women who were experiencing the first onset of PP, along with healthy postpartum participants and non-pregnant age-matched healthy controls ( 53 ).…”
Section: Postpartum Psychosismentioning
confidence: 99%